The Everyday Usage of City-Centre Streets: Urban Behaviour in Provincial Britain ca. 1930–1970 - Faire, Lucy; McHugh, Denise (Urban History Review / Revue d'histoire urbaine, 2014)
This article examines the user experience in the city-centre street space, focusing on three main themes: space usage; the behaviour of users and interventions to direct behaviour by urban authorities; and the sensory and emotional experiences of being on the street. The emphasis is on people’s interaction with the city centre and their perceptions of it. These interactions generated multi-dimensional perspectives linked to individual socio-demographic characteristics producing place-specific experiences. The article uses film, photography and testimony to provide insights into street usage and, while acknowledging that the retail function of the city centre was fundamental, argues that this space generated wider experiences beyond the acquisition of goods and services in commercial transactions. The article concludes that the user experience, behaviour and relationship with the city-centre street are as important to understanding urban function as capital investment and city planning.